Jiwasraya Insurance Default Case: Civil Law Perspective in Consumer Protection - Anwar, Anwar (PT. Anagata Sembagi Education, 2025)
The Jiwasraya Insurance default case raises complex legal implications, especially in the perspective of civil law and consumer protection. The legal relationship between the insurance company and the policyholder, which should be based on the principles of pacta sunt servanda and good faith, turned into a dispute due to violation of contractual obligations and weak supervision. This research uses a normative juridical method with a legislative approach, especially Law Number 40 of 2014 concerning Insurance and Law Number 8 of 1999 concerning Consumer Protection. The results of the analysis show that the civil liability of insurance companies has not been effective due to the weak enforcement of the principles of prudence and transparency in business practices. Legal protection for consumers has also not been optimally implemented due to information inequality, low legal literacy, and lack of intervention by supervisory authorities. It is necessary to reconstruct the principles of civil law that are oriented towards substantive justice and corporate social responsibility so that consumer rights are comprehensively protected. Consistent law enforcement, dispute resolution system reform, and strengthening public legal literacy are key to realizing a transparent, accountable, and fair insurance industry.